2013
DOI: 10.1080/19361521.2013.755652
|View full text |Cite
|
Sign up to set email alerts
|

Relational, Social, and Overt Aggression among Aggressive and Nonaggressive Female Adolescents

Abstract: In this study, researchers wished to further study the differentiation among forms of aggression in a diverse sample of adolescent females. Specifically, the self-reported use of relational, social, and direct verbal and physical aggression was measured in Caucasian and non-Caucasian typically developing versus overtly aggressive adolescent females. No statistically significant differences were found between typically developing and overtly aggressive adolescent female samples in the use of social or relationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…While the standard deviations for the different factors (relational bullying SD = 2.52; social bullying SD = 2.28; overt aggression SD = 1.71) suggest that there is little variance within the different types of bullying or aggression in this sample, the bullying standard deviations fall within the ranges reported in other investigations (e.g., Bell et al 2018;Clinton et al 2014;Comstock et al 2013) and are presented for the readers' reference earlier in the Methods section. However, the standard deviation for the overt aggression factor (SD = 1.71) is smaller than what has been noted in previous studies (e.g., SD = 2.16-3.19), and thus, may present a limitation to the investigation of the hypotheses presented in this study.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…While the standard deviations for the different factors (relational bullying SD = 2.52; social bullying SD = 2.28; overt aggression SD = 1.71) suggest that there is little variance within the different types of bullying or aggression in this sample, the bullying standard deviations fall within the ranges reported in other investigations (e.g., Bell et al 2018;Clinton et al 2014;Comstock et al 2013) and are presented for the readers' reference earlier in the Methods section. However, the standard deviation for the overt aggression factor (SD = 1.71) is smaller than what has been noted in previous studies (e.g., SD = 2.16-3.19), and thus, may present a limitation to the investigation of the hypotheses presented in this study.…”
Section: Resultssupporting
confidence: 61%
“…In other investigations using the YASB or YASB-E, means were reported as or ranging from M = 17.50-21.26 (SD = 2.48-3.55) for the relational bullying scale, M = 20.05-22.76 (SD = 1.72-3.30) for the social bullying scale, M = 14.25 (SD = 4.45) for the interpersonal maturity scale, and M = 6.36-9.17 (SD = 2.16-3.19) for the overt aggression factor of the YASB-E (Bell et al 2018;Clinton et al 2014;Comstock et al 2013). Sample items from the YASB-E include: BWhen I am frustrated with my partner/colleague/ friend, I give that person the silent treatment^and BI criticize people who are close to me^-from the relational bullying factor; BI confront people in public to achieve maximum damage^and BI contribute to the rumor mill at school/work or with my friends/family^-from the social bullying factor; BI respect my friend's opinions, even when they are quite different from my own^and BI deal with interpersonal conflict in an honest, straightforward manner^-from the interpersonal maturity factor; and Bwhen I am mad at someone, I call them mean names^and Bit is okay to hit a friend when you are angry at them^-from the overt aggression factor.…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by Comstock et al (2013), statistically significant differences were found between White girls' (M = 19.32) and non-White girls' (M = 17.50) use of relational aggression as reported through the YASB, with White females demonstrating higher levels of relational aggression, t(24.13) = 2.32, p < .05 (equal variances not assumed because of a statistically significant Levene's test). However, there were no statistically significant differences found between White girls' (M = 21.43) and non-White girls' (M = 20.05) use of social aggression, t(85) = 2.01, p ≥ .05.…”
Section: Downloaded By [University Of Stellenbosch] At 02:52 05 Novemmentioning
confidence: 88%
“…Such behaviours are aimed to cause harm such as threatening, kicking, pushing, hitting, insulting others (Crick & Grotpeter, 1995;Allen & Anderson, 2017). Physical aggression and verbal aggression are considered overt aggression Buss & Perry, 1992;Prinstein et al, 2001;Comstock et al, 2013). On the other hand, relational aggression is known as indirect aggression which refers to social manipulation, damage or threat to damage relationships, gossiping or rumour spreading (Crick, 1995;Crick et al, 2002;Grus, 2003;Werner & Crick, 1999).…”
Section: Introductionmentioning
confidence: 99%